2016
DOI: 10.4254/wjh.v8.i4.231
|View full text |Cite
|
Sign up to set email alerts
|

Portal hypertensive gastropathy: A systematic review of the pathophysiology, clinical presentation, natural history and therapy

Abstract: AIM:To describe the pathophysiology, clinical presentation, natural history, and therapy of portal hypertensive gastropathy (PHG) based on a systematic literature review. METHODS:Computerized search of the literature was performed via PubMed using the following medical subject headings or keywords: "portal" and "gastropathy"; or "portal" and "hypertensive"; or "congestive" and "gastropathy"; or "congestive" and "gastroenteropathy". The following criteria were applied for study inclusion: Publication in peer-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 254 publications
(628 reference statements)
2
74
0
1
Order By: Relevance
“…There is controversy regarding whether or not PHG that occurs in the context of endoscopic therapy is as clinically relevant as the PHG that occurs "spontaneously". Some studies suggest that PHG that occurs after endoscopic sclerotherapy or ligation therapy is transient [2], whilst another study observed no difference in the natural history of PHG whether or not previous endoscopic sclerotherapy therapy was performed [1]. The natural course of PHG after ligation therapy seems to be milder than after sclerotherapy.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is controversy regarding whether or not PHG that occurs in the context of endoscopic therapy is as clinically relevant as the PHG that occurs "spontaneously". Some studies suggest that PHG that occurs after endoscopic sclerotherapy or ligation therapy is transient [2], whilst another study observed no difference in the natural history of PHG whether or not previous endoscopic sclerotherapy therapy was performed [1]. The natural course of PHG after ligation therapy seems to be milder than after sclerotherapy.…”
Section: Discussionmentioning
confidence: 97%
“…The typical location is in the gastric fundus and upper body of the stomach although it can affect the whole stomach and even other areas of the gastrointestinal tract, such as the small bowel or the colon [1]. PHG is one of the major health problems as its prevalence in patients with portal hypertension has been reported to vary between 20% and 80%.…”
Section: Introductionmentioning
confidence: 99%
“…The observed gastric varices were small and lacked SRH, and the bleeding was mild, more consistent with portal hypertensive gastropathy than gastric varices. [58] A prospective clinical series is unlikely because this syndrome is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Portal hypertensive gastropathy (PHG) is clinically important because it is a potential cause of gastric haemorrhage in patients afflicted with portal hypertension (McCormack et al, ; Cubillas and Rockey, ; Han et al, ; Massoni et al, ). Numerous elements, such as portal hypertension, PGs, TNF‐α and NO, have been demonstrated to participate in the pathogenesis of PHG (Patwardhan and Cardenas, ; Gjeorgjievski and Cappell, ). Gastric mucosal apoptosis is involved in PHG, and p53‐up‐regulated modulator of apoptosis (PUMA) plays a vital role in endoplasmic reticulum (ER) stress‐induced mucosal epithelial apoptosis in PHG (Tan et al, ).…”
Section: Introductionmentioning
confidence: 99%